2007
DOI: 10.1021/jp0619538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cholesterol and Other Additives on Viscosity, Self-Diffusion Coefficient, and Intramolecular Movements of Oleic Acid

Abstract: It has been empirically known that cholesterol largely increases the viscosity of oleic acid. To clarify the mechanism of the effect of cholesterol on the intermolecular and the intramolecular (segmental) movements of oleic acid in the liquid state, we measured density, viscosity, IR, 1H NMR chemical shift, self-diffusion coefficient, and 13C NMR spin-lattice relaxation time for the liquid samples of oleic acid containing a small amount of cholesterol. Furthermore, the above measurements were also carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The value of D B , the bulk diffusion coefficient of Span 80 in Marcol 52 oil, is not known. Since the Span 80 molecule is not much larger than the alkanes in the oil, we may use as a rough estimate the self-diffusion coefficient of the tail of the Span 80 molecule, namely oleic acid, which gives D B ≈ 10 −10 m 2 /s (Iwahashi et al, 2007); of the same order of magnitude as e.g. the diffusion coefficient of C 12 E 6 surfactant in water (Lin et al, 2003).…”
mentioning
confidence: 99%
“…The value of D B , the bulk diffusion coefficient of Span 80 in Marcol 52 oil, is not known. Since the Span 80 molecule is not much larger than the alkanes in the oil, we may use as a rough estimate the self-diffusion coefficient of the tail of the Span 80 molecule, namely oleic acid, which gives D B ≈ 10 −10 m 2 /s (Iwahashi et al, 2007); of the same order of magnitude as e.g. the diffusion coefficient of C 12 E 6 surfactant in water (Lin et al, 2003).…”
mentioning
confidence: 99%
“…These characteristic APS peaks are also observed in both OA‐modified APS [Figure (b)] and silane‐modified APS [Figure (c)]. The broad stretching vibration peak at 1650–1750 cm −1 is assigned to the carboxyl group of OA [Figure (b)] . The absorption peaks of asymmetry stretching vibration of CH at 2971, 2927 cm −1 , which exist in the spectra of Figure (c), are attributed to KH‐570 [Figure (d)].…”
Section: Resultsmentioning
confidence: 90%
“…OA is a long-chain carboxylic acid that is an important component of biological substances, and has already been well characterized by using NIR and mid-IR spectroscopy. 2431 The association and dissociation of OA in the liquid state has been particularly well studied. 2427,30,31 Iwahashi et al 24 investigated the temperature dependence of the NIR band at 6919 cm −1 and found that the dissociation of dimers occurred even in the pure liquid state.…”
Section: Introductionmentioning
confidence: 99%
“…2431 The association and dissociation of OA in the liquid state has been particularly well studied. 2427,30,31 Iwahashi et al 24 investigated the temperature dependence of the NIR band at 6919 cm −1 and found that the dissociation of dimers occurred even in the pure liquid state. Shinzawa and Noda 30 recorded time-dependent mid-IR spectra of a binary mixture of OA and carbon tetrachloride by using the ATR method, and documented the dynamic behavior of OA molecules undergoing self-assembly into smectic liquid crystals in detail via 2D-COS in conjunction with an eigenvector manipulating transformation technique.…”
Section: Introductionmentioning
confidence: 99%